Noble Metal Nanomaterial-Based Biosensors for Electrochemical and Optical Detection of Viruses Causing Respiratory Illnesses - Choi, Hye Kyu; Lee, Myeong-Jun; Lee, Sang Nam; Kim, Tae-Hyung; Oh, Byung-Keun (Frontiers in Chemistry, 2021)
Noble metal nanomaterials, such as gold, silver, and platinum, have been studied a lot in broad scientific fields because of their unique properties, including superior conductivity, plasmonic property, and biocompatibility. Due to their unique properties, the researchers have used them to fabricate biosensors. Recently, the biosensors for the detection of respiratory illness-inducing viruses have gained attention after the global outbreak of coronavirus disease (COVID-19). In this mini-review, we will discuss noble metal nanomaterials and biosensors based on them for detecting respiratory illness-causing viruses, including SARS-CoV-2, using electrochemical and optical detection techniques. In conclusion, this review will provide interdisciplinary knowledge about the application of noble metal nanomaterials to the biomedical field.